Determining value of Coordinated Registry Networks (CRNs): a case of transcatheter valve therapies. Issue 1 (4th July 2019) - Pappas, Gregory; Berlin, Jesse; Avila-Tang, Erika; Carroll, John; Drozda, Joseph; Dumont, Douglas; Gross, Thomas; Hewitt, Kathleen; Kirtane, Ajay; Kong, David; Krucoff, Mitchell; Lashinger, John; et al.
Abstract : Background: The Transcatheter Valve Therapy (TVT) Coordinated Registry Network (CRN) supported 23 regulatory decisions and ensured evidence-based evaluation of the application of TVT technology. However, there are cost concerns that require value assessment of the TVT CRN compared with traditional study designs. Objectives: We aimed to determine the value created by the TVT CRN based on (1) Return on investment (ROI), (2) Time saved (TS) in conducting necessary regulatory studies. Methods: For both ROI and TS analyses, we compared studies that used the TVT CRN with those that would have been required if the registry did not exist (counterfactual studies). To estimate ROI, we accounted for the costs of investment and gain from investment. Both the counterfactual costs and length of studies were projected using design specifications determined by US Food and Drug Administration (FDA) reviewers. Results: We identified 21 studies using the TVT CRN (supporting 23 FDA decisions) that generated evidence on TVT for three device manufacturers. ROI is estimated to be greater than 550%. TS by using the CRN ranged from months to years. Conclusions: The CRN method to evidence generation creates value for manufacturers and the broader device ecosystem, demonstrated with this example of the TVT CRN. The public health benefits of evidence created by this CRN outweighs the difference in data quality between traditional clinical studies and the CRN method.